Synergistic effects of Na+-montmorillonite and multi-walled carbon nanotubes on mechanical properties of chitosan film (eXPRESS Polymer Letters, 2009)
Chitosan/Na+-montmorillonite/multi-walled carbon nanotubes (CTS/MMT/MWCNTs) nanocomposite films were prepared by a simple solution-evaporation method. The effects of MMT and MWCNTs on mechanical properties of the nanocomposite films were investigated. The results indicate that the simultaneously introduced MMT and MWCNTs into CTS film could greatly improve the mechanical properties. The Young’s modulus of the CTS film is increased about 50% as 1.0 wt% MMT and 1.0 wt% MWCNTs are introduced. The MMT could compensate the negative effect of MWCNTs on elongation at break of the CTS film. The highest elongation at break is obtained when the contents of MMT and MWCNTs are 0.5 and 0.5 wt%, respectively. Formation of the MMT…CTS…MWCNTs subassembly may be responsible for the observed synergistic effect of MMT and MWCNTs on mechanical properties of the CTS film.